A resolução de problemas, a modelagem matemática e desenvolvimento de habilidades matemáticas em alunos do 7º ano do ensino fundamental - Zequim, Katia Cristina (Universidade Federal de São Carlos, 2014)
In recent years, much has been said of the need to improve the quality of education. Specifically in mathematics, the quest for change has been to approximate contents of schooling of everyday problems of students. Nowadays, teaching mathematics is restricted basically in memorizing formulas and resolution of repetitive exercises. The central question to be answered in this research, level Professional Master, is "learning activities, based on Problem Solving and Mathematical Modelling, contribute to the development of mathematical skills in students of 7th year of elementary school?". To help find the answer to this question, two specific questions were proposed: (1st) "What difficulties encountered during the planning, development and implementation of educational activities of research?", and, (2nd) "What is the contribution that research brought to my teacher training in mathematics, didactic and methodological prospects?". The survey results showed that of the 16 math skills selected for investigation, 6 of them worked and were evaluated at 3 or 4 of the planned and implemented educational activities. These six, five of them are associated with "power to carry out" this basic competence and processes necessary for the development of problem-solving and mathematical modelling. Therefore, the conclusion of research on the key issue is that "yes, problem solving and mathematical modelling contributed much to the development of mathematical skills in students from the 7th year of elementary school, involved in research." About the difficulties faced during the course of the research, the main one was to put on paper, in writing, what was being planned in the teaching activities, the observations made during the applications of these activities on students and everything needed report coherently in this dissertation. Finally, the main contribution that research has brought into my teacher training refers to the teaching perspective. Through research, she realized that the act of teaching mathematics can from practice and contextualized problem situations and, consequently, more meaningful and attractive to students. Came to believe that, at least in formal education, mathematics should be taught as a "tool" that, when used well, helps us to better understand the society in which we live.
Keywords: Matemática - estudo e ensino; Ensino fundamental; Resolução de problemas; Modelagem matemática; Habilidades matemáticas; Sequência didática; Problem solving; Mathematical modelling; Mathematical skills; Sequence of teaching activities; CIENCIAS EXATAS E DA TERRA